Improving the Assessment and Classification of Sick Children according to the Integrated Management of Childhood Illness (IMCI) Protocol at Sanja Primary Hospital, Northwest Ethiopia: A Pre-Post Interventional Study - Mohammed Abayneh; Tsegaye Gebremedhin; Endalkachew Dellie; Chalie Tadie Tsehay; Asmamaw Atnafu (International Journal of Pediatrics)
Background. A complete and consistent use of integrated management of childhood illness (IMCI) protocol is a strategic implementation that has been used to promote the accurate assessment and classifications of childhood illnesses, ensures appropriate combined treatment, strengthens the counseling of caregiver, and speeds up the referrals to decrease child mortality and morbidity. However, there is limited evidence about the complete and consistent use of IMCI protocol during the assessment and classifications of childhood illness in Ethiopia. Therefore, this intervention was implemented to improve the assessment and classifications of childhood illness according to the IMCI protocol in Sanja primary hospital, northwest Ethiopia. Methods. A pre-post interventional study was used in Sanja primary hospital from January 01 to May 30, 2019. A total of 762 (381 for pre and 381 for postintervention) children from 2 months up to 5 years of age were involved in the study. Data were collected using a structured questionnaire prepared from the IMCI guideline, and a facility checklist was used. A five-month in-service training, weekly supportive supervision, daily morning session, and availing essential drugs and materials were done. Both the descriptive statistics and independent t-test were done. In the independent t-test, a p value of <0.05 and a mean difference with 95% CI were used to declare the significance of the interventions. Results. The findings revealed that the overall completeness of the assessment was improved from 37.8 to 79.8% (mean difference: 0.17; 95% CI: 0.10-0.22), consistency of assessment with classification from 47.5 to 76.9% (mean difference: 0.34; 95% CI: 0.27-0.39), classification with treatment from 42.3 to 75.4% (mean difference: 0.35; 95% CI: 0.28-0.47), and classification with follow-up from 32.8 to 73.0% (mean difference: 0.36; 95% CI: 0.29-0.42). Conclusion. The intervention has a significant improvement in the assessment and classification of childhood illness according to the IMCI protocol. Therefore, steps must be taken to ensure high quality of training, adequate supervision including the observation of health workers managing sick children during supervisory visits, and a constant supply of essential drugs and job aids for successful implementation of IMCI in the hospital and also to other facilities.